Etika dan Efek Komunikasi Politik Pada Pemilu Di Indonesia - Anisa, Resi; Darmawan, Rio Surya; Rahmawati, Sarah Silpia; Nisa, Syifa Atqiyatun; Maulana, Wendi (SIYASI: Jurnal Trias Politica, 2023)
Abstract            Ethics and the Effects of Political Communication on Elections in Indonesia is a very comprehensive and very broad discussion and does not only discuss how to understand the basics but we will try to understand and implement it internally to gain power and political goals. In making this journal, library research became the research method chosen by the author, namely by utilizing existing sources in the library to obtain research data. Besides that, to make writing easier for this journal, the method of content analysis is the choice used by the author, who focuses on reading and examining the contents of the source to be studied, which is also used as a reference for making this journal. In communication, you really need something called ethics for the purposes and objectives to be conveyed in communicating. In the context of parliamentary elections, political communication plays a very important role. The role of political communication in elections, for example: First, Increase the number of people who are interested in and follow the message conveyed by the people's representatives. Second Increasing the followers of political communicators increases the vote in elections. Third Adding followers and the number of people that can be formed through the opinions formed by political communicators. Fourth Expanding sympathy for the performance in the vision and mission of the candidates participating in the election. And finally, fifth, as a medium for socializing candidacy as a people's representative. Communication is the main key to general elections, people's representatives who want to run for office must communicate well and be sure that this communication is called political communication. AbstrakEtika dan Efek Komunikasi Politik Pada Pemilu di Indonesia merupakan bahasan yang sangat komprehensif dan sangat luas dan tidak hanya membahas bagaimanapada pemahaman dasar akan tetapi kita akan mencoba untuk memahami dan mengimplementasikan secara internal untuk meraih kekuasaan serta tujuan politik. Dalam pembuatan jurnal ini studi kepustakaan (library research) yang menjadi Metode penelitian yang dipilih oleh penulis, yakni dengan memanfaatkan sumber yang ada diperpustakaan guna memperoleh data penelitian. Disamping itu untuk mempermudah penulisan jurnal ini metode analisis isi (content analysis) menjadi pilihan yang digunakan oleh penulis, yang berfokus pada membaca dan mencermati isi dari sumber yang akan diteliti juga dijadikan referensi pembuatan jurnal ini. Dalam komunikasi, sangat memerlukan yang namanya etika guna maksud dan tujuan yang ingin disampaikan dalam berkomunikasi tersampaikan. Dalam konteks pemilihan parlemen, komunikasi politik memegang peranan yang sangat penting. Peran komunikasi politik dalam pemilu misalnya: Pertama, Meningkatkan jumlah orang yang tertarik dan mengikuti pesan yang telah disampaikan oleh wakil rakyat. Kedua Meningkatkan pengikut dari komunikator politik meningkatkan suara dalam pemilihan umum. Ketiga Menambah pengikut dan jumlah orang yang dapat dibentuk melalui opini yang dibentuk oleh komunikator politik. Keempat Memperluas simpati akan kinerja dalam visi misi calon peserta pemilu. Dan terakhir yang kelima Sebagai media untuk sosialisasi pencalonan sebagai wakil rakyat. Komunikasi adalah kunci utama pemilihan umum, wakil rakyat yang ingin mencalonkan diri harus berkomunikasi dengan baik juga meyakinkan yang mana komunikasi ini disebut komunikasi politik.